The Six Dimensions of Value Associated to the use of Copernicus Sentinel Data: Key Findings From the Sentinel Benefits Study - Sawyer, Geoff; Mamais, Eleftherios; Papadakis, Dimitri (Frontiers in Environmental Science, 2022)
The role of Earth Observation (EO) data from satellites in supporting informed decision-making and more efficient operational processes is becoming increasingly recognized. However, analysing the value that this generates remains a challenge. Often, top-down cost-benefit analyses are used to justify budgets but with very broad-based, macro-economic assumptions. The approach discussed in this paper is bottom-up building on the use of a single product or service arising from the use of data coming from one or more of the Copernicus Sentinel satellites. This allows a much finer, detailed understanding of how the data is being used and hence contributing to informed decision making. A case-based, value-chain methodology has been applied through which the impact on society can be analysed. Whilst early cases focused on economic value ie monetized benefits, later ones recognise that often the benefits may be wider than this. For instance, organisations can benefit through an increased reputation, or societal values such as quality of life can be felt. Consequently, a set of non-monetary dimensions have been defined which provide a new framework for the analysis. The 6 dimensions are described in the paper and have been tested on a significant number of recent cases. The paper describes the updated methodology and the results obtained through its application.